ANALISIS PERBANDINGAN MODEL PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI LAUT - Izzati Ramadhani; R.A. Norromadani Yuniati; Irma Rustini Aju (Proceeding Maritime Business Management Conference, 2023)
Financial distress is the financial difficulty experienced by a company to cover its obligations, starting with mild difficulties to more serious difficulties. Various analyzes have been developed to predict the early bankruptcy of companies, for example, the Altman ZScore Model, Springate, Zmijewski, Grover, Ohlson, Fulmer, and so on. This study uses the Springate, Grover, and Zmijewski models. This study aims to determine the difference between the Springate, Grover and Zmijewski models in predicting financial distress in sea freight transportation sub-sector companies in Indonesia. The population in this study were 28 companies and 9 companies were used as samples based on purposive sampling technique. This study uses Wilcoxon Signed Ranked with the help of the SPSS program to compare the three models, and the results obtained are that there are differences between the Springate and Grover models, there are differences between the Springate and Zmijewski models, but there are no differences between the Grover and Zmijewski models. The existenceof significant differences in financial distress prediction models can be taken into consideration in choosing a good prediction model